Strategi Pengembangan Pasar Tradisional Di Desa Wisata Pantai Labu Berbasis Kearifan Lokal Pada Era Digital 4.0 - Fijrina, Firly; Nurjannah, Siti; Br Pasaribu, Umy Wulandari; Br Ginting, Wendamia Hafni; Pardede, Citra Bunga Lestari; Mawaddah, Arum; Firmansyah, Wira (Jurnal Ilmiah Dikdaya, 2025)
This study highlights Pasar Kamu in Desa Denai Lama, Pantai Labu, Deli Serdang, as an example of a traditional market that promotes local wisdom through culinary and cultural activities. Using a qualitative approach with ethnographic methods based on Spradley’s techniques, this research involves ethnographic interviews, domain analysis, and taxonomic analysis. Data were collected through non-participant observation, interviews with market stakeholders, and literature reviews. The findings reveal that Pasar Kamu successfully attracts visitors with unique features such as tempu currency (made from coconut shells), digital promotions, and cultural performances. Despite its popularity, the market faces challenges such as limited infrastructure, unfavorable weather, and inconsistent government support. Recommended strategies include preserving authentic traditional cuisine, implementing eco-friendly practices, and engaging local youth in market management. This study underscores Pasar Kamu as a model for integrating cultural preservation and economic development in the digital era, providing insights into how traditional markets can compete while maintaining local identity.